Performance of Electro-Fenton Process for Phenol Degradation Using Nickel Foam as a Cathode - Thwaini, Hind H.; Salman, Rasha H.; Abdul-Majeed , Wameath S. (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
Toxic substances have been released into water supplies in recent decades because of fast industrialization and population growth. Fenton electrochemical process has been addressed to treat wastewater which is very popular because of its high efficiency and straightforward design. One of the advanced oxidation processes (AOPs) is electro-Fenton (EF) process, and electrode material significantly affects its performance. Nickel foam was chosen as the source of electro-generated hydrogen peroxide (H2O2) due to its good characteristics. In the present study, the main goals were to explore the effects of operation parameters (FeSO4 concentration, current density, and electrolysis time) on the catalytic performance that was optimized by response surface methodology (RSM). According to the results, nickel foam made an excellent choice as cathode material. The pH value was adjusted at 3 and the airflow at 10 L/h for all experiments. It was found that the optimal conditions were current density of 4.23 mA/cm2, Fe2+ dosage of 0.1 mM, and time of 5 h to obtain the removal rates of phenol and chemical oxygen demand (COD) of 81.335% and 79.1%, respectively. The results indicated that time had the highest effect on the phenol and COD removal efficiencies, while the impact of current density was the lowest. The high R2 value of the model equation (98.03%) confirmed its suitability.